2002
DOI: 10.1007/s00412-002-0182-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin, HP1 and methylation at lysine 9 of histone H3 in animals

Abstract: We show that methylated lysine 9 of histone H3 (Me9H3) is a marker of heterochromatin in divergent animal species. It localises to both constitutive and facultative heterochromatin and replicates late in S-phase of the cell cycle. Significantly, Me9H3 is enriched in the inactive mammalian X chromosome (Xi) in female cells, as well as in the XY body during meiosis in the male, and forms a G-band pattern along the arms of the autosomes. Me9H3 is a constituent of imprinted chromosomes that are repressed. The pate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
240
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(261 citation statements)
references
References 101 publications
19
240
0
2
Order By: Relevance
“…This is consistent with the dynamic nature of HP1 binding to heterochromatin (9,17,18). The loss of ING1 or DMAP1 impinges on the integrity of heterochromatin, which in turn is likely to change the dynamics of HP1 binding.…”
Section: Fig 3-continuedsupporting
confidence: 79%
See 1 more Smart Citation
“…This is consistent with the dynamic nature of HP1 binding to heterochromatin (9,17,18). The loss of ING1 or DMAP1 impinges on the integrity of heterochromatin, which in turn is likely to change the dynamics of HP1 binding.…”
Section: Fig 3-continuedsupporting
confidence: 79%
“…To test this possibility, we used small RNA interference to silence ING1 and Sin3 and examined the effect of siRNA on the organization of heterochromatin by analyzing localization of two heterochromatin markers, HP1␣ and trimethylated histone H3 at K9. Recent work on heterochromatin histone modifications found that the trimethylated H3K9 may also be used as a heterochromatin marker in immunofluorescence (9,15). HP1␣ and trimethyl-K9 form distinct, large and small foci and co-localize in siVimentin-transfected control cells (Fig.…”
Section: P33ing1-sin3 and Dnmt1-dmap1 Complexes Are Required For Hetementioning
confidence: 97%
“…Cross-linking was quenched with 1.25 M glycine and genomic DNA was sonicated. 24 For precipitation the following antibodies were used: anti-H3K9me3, 25 anti-H4K20me3, 9 antiH3ac (#06-599, Upstate, Temecula, CA), anti-H3-K9ac (#07-352, Upstate), anti-H3K4me3 (#07-473, Upstate) and rabbit normal serum (#011-000-001, Dianova, Hamburg, Germany). Purified DNA fragments were quantified by real-time PCR [LightCycler 1.5 and FastStart DNA Master SYBR Green I Kit (Roche, Mannheim, Germany)] with the following forward and reverse primers, respectively: CD14(-150), TTA GGC TCC CGA GTC AAC AG, AGG GCA TCT AGG GTT CTG TG; CD14 (+150), GTA GGG TCT TGG GGT CGA A, AGG TCT AGG AGG CCC CAT C; CD14 (+300), GCT GGA CGA TGA AGA TTT CC, GGC ATG GAT CTC CAC CTC TA; CD14 (+1150), GCT CAG AGT GCT CGA TCT CA, CCC GTC CAG TGT CAG GTT AT; CD209 (-1550), TTG AGG AGC AGG TTC TTT AG, ACC TAG AAG TTC CCA CCT GT; CD209 (-500), AGT GCC TCC TCA GTT TCC, AAT GCC TAG GGT AGT CAG GT; CD209 (+1), ATC ACA GGG TGG GAA ATA A, AGT CTT GGT TCC TTG GAG TC; CD209 (+300), GAG ACG AGA GAC TCC TGG AC, AAA CTC AAC CTC CTC AGG TC; CD209 (+1000), CTG GTG CTG CAA CTC CTC, TGT GTC CAC AGC CAA AAG; CD209 (+2500), GGA CAT TCT TCC AAG GAA AC, CTC AGC ACT TTT GAT TAC GA; LINE-5, CAG AAT TTC ATA TCC AGC CA; LINE-3, GCA GGC CTG GTG GTG AC; H4 Strukturgen F: CAT CAC CAA GCC TGC CAT TCG G; H4 Strukturgen Rev, CAC ATC CAT GGC TGT GAC GGT C. For calculation of the precipitated fraction we used an input control which was not subjected to immunoprecipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-dimethylated Lys 4 and acetylated Lys 14 histone H3 polyclonal antibodies were purchased from Upstate Biotechnology, Inc. (Lake Placid, NY). The characterization of anti-trimethylated Lys 9 histone H3 antibodies has been described (22). Affinity-purified secondary * This work was supported by grants from the Association Francaise contre les Myopathies (France) and the General Secretariat of Research and Technology (Greece) (to S. D. G.), a core grant from the Biotechnology and Biological Sciences Research Council (United Kingdom) (to P. B. S.), a Royal Society (United Kingdom) exchange award (to P. B. S. and S. D. G.), and National Institutes of Health Grant CA20408 (to L. D. S.).…”
Section: Methodsmentioning
confidence: 99%